Migration, Unemployment and the Business Cycle - A Euro Area Perspective - Marius Clemens (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
In the recent European debt crisis, internal migration flows in the euro area reacted strongly to diverging labor market conditions. This experience points towards the prominent role of short-term business-cycle migration in the euro area and the consequent need to understand the motives behind it. Investigating the business cycle in 55 bilateral migration corridors in the euro area over the period 1980-2010, we find evidence for business cycle related fluctuations in net migration flows and the crucial role of unemployment in shaping migration patterns. While on average wage and unemployment differentials are negatively correlated with net migration, across migration corridors we document a considerable heterogeneity in both dimensions that is more pronounced for wages. In line with these findings, we built a two-country dynamic stochastic general equilibrium (DSGE) model of internal business cycle migration in the euro area and allow for unemployment that occurs as a consequence of labor market frictions and rigidities in both countries. Our model is able to replicate the empirical observations and explains the heterogeneity of migration corridors by differences in the type of shock that hits an economy and the relative price/wage rigidity. We contribute to the literature on the causes and consequences of temporary migration and bridge it to DSGE models with unemployment.
Keywords: E24; F22; F41; 330